Cyclodextrin type dependent host-guest interaction mode with phthalocyanine and their influence on photodynamic activity to cancer. (5th September 2016) - Lu, S.; Wang, A.; Ma, Y.J.; Xuan, H.Y.; Zhao, B.; Li, X.D.; Zhou, J.H.; Zhou, L.; Wei, S.H.
Highlights: Cyclodextrins (CD) can form stable 4:1 host-guest complexes with ZnPc. Three host-guest complexes of ZnPc with α-, β- and γ- CD were prepared and compared. The interaction mode between ZnPc and various CDs were obvious different. The anticancer activity of complexes were superior to free ZnPc. Complex of β-CD and ZnPc has best anticancer activity than two of other complexes. Abstract: Three host-guest complexes of phthalocyanines (Pc) with α-, β- or γ-cyclodextrins (CDs) were prepared and their interaction modes, reactive oxygen species (ROSs) generation ability and in vitro anticancer activities were studied and compared. After forming complex with CD, the aggregation degree of Pc was greatly decreased and the water solubility and photodynamic activity was sharply increased. Computer modeling results indicated that the interaction modes between Pc and CDs were varied with different kinds of CD. Especially, the complex of Pc and β-CD has superior stability, ROSs generation ability, and anticancer activity to other complexes.